2016
DOI: 10.1371/journal.pone.0156853
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Mineral Oil-Based Head Lice Shampoo: A Randomized, Controlled, Investigator-Blinded, Comparative Study

Abstract: BackgroundDue to increased resistance and safety concerns with insecticide-based pediculicides, there is growing demand for head lice treatments with a physical mode of action. Certain mineral oils kill lice by blocking spiracles or by disrupting the epicuticular wax layer. The present study was performed to evaluate efficacy and safety of a mineral oil-based shampoo.MethodsThis randomized, controlled, investigator-blinded, monocentric study (EudraCT registration no. 2014-002918-23) was performed from October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…In addition, the failure of current chemical treatments to kill lice embryos in eggs, the environmental and food safety concerns posed by these treatments, and their potential toxicity to users necessitate the development of safe alternative treatment methods that can effectively kill adult lice and eggs via new modes of action [15,16], Other causes for the development of resistance to existing pediculicides include the persistence of pediculicide residue on hair, exposure of lice to sub-therapeutic concentrations, and inadequate concentration levels [5,6]. Numerous studies of the different types of head lice treatments have revealed that commercial pediculicides are ineffective in treating head lice infestations in students [12][13][14][17][18][19]. genetic mutations in the lice, which we plan to investigate in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the failure of current chemical treatments to kill lice embryos in eggs, the environmental and food safety concerns posed by these treatments, and their potential toxicity to users necessitate the development of safe alternative treatment methods that can effectively kill adult lice and eggs via new modes of action [15,16], Other causes for the development of resistance to existing pediculicides include the persistence of pediculicide residue on hair, exposure of lice to sub-therapeutic concentrations, and inadequate concentration levels [5,6]. Numerous studies of the different types of head lice treatments have revealed that commercial pediculicides are ineffective in treating head lice infestations in students [12][13][14][17][18][19]. genetic mutations in the lice, which we plan to investigate in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Grade 2 or medium (10 to 25 nit or live nymphs/lice); 4. Grade 3 or severe (more than 25 nit or live nymphs/lice) [25,30]. All examinations were performed 4 times; once before the treatment (day zero) and 3 times after the start of treatment (days 4, 10, 14).…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…The inclusion criteria included avoiding depriving patients of routine treatment, patients who had used permethrin treatment twice and more consecutively (with at least 14 days interval) according to the correct instructions (on the first and 7 th day) and did not respond to treatment, and yet they had at least grade 1 infection (5-9 nit or live nymphs/lice); they were selected as subjects of the study according to the severity of the contamination [25]. Although the second line of treatment is based on Lindane therapy, the resistance to Lindane is also very high [2,8].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The hair was divided into 4 quadrants by a plastic head lice comb. Next, the hair on each quadrant was combed 6 times starting from the scalp and ending at the hair tips [ 21 ]. The number of lice collected was counted.…”
Section: Methodsmentioning
confidence: 99%